Teacher And Student Book Analysis Integrated Thematic Character of Pancasila Student Profile in Grade I SD or MI Theme I is Myself - Suharsiwi; Novia Sari (Lembaga Penelitian dan Publikasi Ilmiah (LPPI), Yayasan Yuta Pendidikan Cerdas, 2023)
This study aims to determine: 1) to find out the literature review of thematic teacher books integrated character profiles of Pancasila students in grade I SD or MI Theme I Myself. 2) to find out the literature review of thematic students' books integrated with the character profile of Pancasila students in grade I SD or MI Theme I Myself. The research approach used is a qualitative library research approach or library research. The type of research used in this research is text study or textbook analysis. Analysis of textbooks in the form of integrated thematic teacher and student books for the 2013 curriculum for grade 1 SD or MI theme 1: myself. The results of the study show that: 1) In the thematic teacher's book integrated curriculum 2013 grade 1 SD or MI Theme 1: Myself, there are 14 character values. The 14 character values are discipline, friendly or communicative, religious, honest, hard work, independent, responsible, tolerance, curiosity, love to read, creative, national spirit, love for the homeland, and caring (social care). In the values of the Pancasila student profile there are all or there are 6 indicators or values of the Pancasila student profile. The 6 values of the Pancasila student profile are faith and piety to God Almighty and noble character, mutual cooperation, independence, global diversity, critical reasoning, and creativity. 2) In the thematic integrated student book 2013 curriculum grade 1 SD or MI Theme 1: Myself, there are 10 character values. The 10 character values are religious, friendly or communicative, hard work, independent, responsible, disciplined, love to read, creative, love the homeland, and tolerance. In the values of the Pancasila student profile, there are all or 6 indicators or values of the Pancasila student profile. The 6 values of the Pancasila student profile are faith and piety to God Almighty and noble character, mutual cooperation, independence, global diversity, critical reasoning, and creativity.